Carotid body Tumour with Hypoglossal Nerve Palsy- A Case Report (Bangladesh Heart Journal, 2019)
Objective: Carotid body tumour is a rare tumour. This is a case report of carotid body tumour of the right side involving the right hypoglossal nerve with MRI appearance and pathological features. The objective is to present a case of Hypoglossal nerve palsy due to carotid body tumour involving the right carotid artery bifurcation.Method: A 18-year old male presented with a welldefined swelling of his right neck, increasing hoarseness, and left ward tongue deviation on protrusion present for two years CT neck and MRI were done. The tumour was identified and the patient underwent surgery. His Histopathology report commented it to be carotid body tumour.Result: The patient showed significant improvement after surgery. His tongue deviation improved and his hoarseness of voice had been begun to improve.Conclusion: Carotid body tumours are benign lesion mimicking other pathology. High level of suspicision, imaging and careful resection is important for avoiding complications.Bangladesh Heart Journal 2019; 34(1) : 68-72